Prediction of malignant middle cerebral artery infarction by magnetic resonance imaging within 6 hours of symptom onset: a prospective multicenter observational study - Thomalla, Götz; Hartmann, Frank; Jüttler, Eric; Singer, Oliver C.; Lehnhardt, Fritz-Georg; Köhrmann, Martin; Kersten, Jan Felix; Krützelmann, Anna; Humpich, Marek C.; Sobesky, Jan; Gerloff, Christian; Villringer, Arno; et al. (Annals of neurology, 2010)
Objective Early identification of patients at risk of space-occupying “malignant” middle cerebral artery (MCA) infarction (MMI) is needed to enable timely decision for potentially life-saving treatment such as decompressive hemicraniectomy. We tested the hypothesis that acute stroke magnetic resonance imaging (MRI) predicts MMI within 6 hours of stroke onset. Methods In a prospective, multicenter, observational cohort study patients with acute ischemic stroke and MCA main stem occlusion were studied by MRI including diffusion-weighted imaging (DWI), perfusion imaging (PI), and MR-angiography within 6 hours of symptom onset. Multivariate regression analysis was used to identify clinical and imaging predictors of MMI. Results Of 140 patients included, 27 (19.3%) developed MMI. The following parameters were identified as independent predictors of MMI: larger acute DWI lesion volume (per 1 ml odds ratio [OR] 1.04, 95% confidence interval [CI] 1.02-1.06; p < 0.001), combined MCA + internal carotid artery occlusion (5.38, 1.55-18.68; p = 0.008), and severity of neurological deficit on admission assessed by the National Institutes of Health Stroke Scale score (per 1 point 1.16, 1.00-1.35; p = 0.053). The prespecified threshold of a DWI lesion volume >82 ml predicted MMI with high specificity (0.98, 95% CI 0.94-1.00), negative predictive value (0.90, 0.83-0.94), and positive predictive value (0.88, 0.62-0.98), but sensitivity was low (0.52, 0.32-0.71). Interpretation Stroke MRI on admission predicts malignant course in severe MCA stroke with high positive and negative predictive value and may help in guiding treatment decisions, such as decompressive surgery. In a subset of patients with small initial DWI lesion volumes, repeated diagnostic tests are required. ANN NEUROL 2010